The Laboratory Diagnosis of Syphilis - Sam Ratnam (Canadian Journal of Infectious Diseases and Medical Microbiology)
Syphilis has several clinical manifestations, making laboratory testing a very important aspect of diagnosis. In North America, many unsuspected cases are discovered by laboratory testing. The etiological agent, Treponema pallidum, cannot be cultured, and there is no single optimal alternative test. Serological testing is the most frequently used approach in the laboratory diagnosis of syphilis. The present paper discusses the various serological and alternative tests currently available along with their limitations, and relates their results to the likely corresponding clinical stage of the disease. The need to use multiple tests is discussed, and the importance of quality control is noted. The complexity of syphilis serology means that the services of reference laboratories and clinical experts are often needed.